Experimental investigation on an air source heat pump system with coupled liquid-storage gas-liquid separator regarding heating and defrosting performance. (February 2022) - Ma, Longxia; Wang, Fenghao; Wang, Zhihua; Zhang, Sheng; Liu, Zixuan; Lou, Yechun
Highlights: Heating and defrosting performance of air source heat pump with liquid storage gas-liquid separator is experimentally studied. Outdoor coil temperature and suction temperature of compressor influences system frosting performance. The reason why the proposed system delays frosting was analyzed. The reason why the proposed system reduces frosting time was analyzed. Abstract: Air source heat pump (ASHP) has advantages of high efficiency, eco-friendly operation, and convenient installation, but frost accumulation on the outdoor heat exchanger is one of the basic concerns about its operation. Reverse cycle defrosting (RCD) is widely used for defrosting, however, when RCD begins and ends, the four-way reversing valve quickly switches and the system pressure needs to be rebalanced which will cause the incomplete evaporation of refrigerant into the compressor. Thus, it leads to the decrease of the performance of the ASHP system during RCD. In order to improve the performance of RCD, this study proposes an ASHP defrosting system with coupled liquid-storage gas-liquid separator. An obvious advantage of the proposed system is retarding frosting, reducing defrosting time and increasing the heating capacity and coefficient of performance (COP) of the ASHP system thus reducing the number of defrosting cycles. And the proposed system can improve indoor thermal comfort during defrosting. Experiments show that compared with the original system, the proposed system delays frosting by 30 min and reduces the defrosting time by 74 s (22.7%), improving the heating capacity and COP by 6.78% and 12.8% respectively. Moreover, the proposed system with the coupled liquid-storage gas-liquid separator is economically friendly, which further benefits its practical applications.